ON THE EFFICIENCY OF THE APPLICATION OF CREATIVE TASKS (BASED ON WORKS OF FICTION) - Umida Ramazonovna PULATOVA (Scholar Express Journals, 2023)
The article focuses on a set of tasks developed on the material of works of fiction. In particular, the works proposed for study are considered as a means of learning. Tasks developed on their basis are aimed at developing linguistic and some professional skills in law students
Keywords: task; document; analysis; written speech